2023
DOI: 10.1101/2023.02.14.528531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metformin impairs trophoblast metabolism and differentiation in dose dependent manner

Abstract: Metformin is a widely prescribed medication whose mechanism of action in not completely defined and whose role in gestational diabetes management remains controversial. In addition to increasing risks of fetal growth abnormalities and preeclampsia, gestational diabetes is associated with abnormalities in placental development including impairments in trophoblast differentiation. Given that metformin impacts cellular differentiation events in other systems, we assessed metformin's impact on trophoblast metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Gestational diabetes causes placental immaturity, necrosis, and hyper-angiogenesis ( Jarmuzek et al, 2015 ), and is linked with offspring developmental delay ( Sun et al, 2022 ) and cognitive dysfunction ( Ahmed et al, 2023 ; Van Dam et al, 2018 ), among other neurodevelopmental outcomes ( Shao et al, 2021 ) revealed by clinical studies. The gestational diabetes medication metformin is also linked to placental metabolic and differentiation phenotypes ( Nashif et al, 2023 ) as well as child neurodevelopmental abnormalities ( Deussen et al, 2023 ; Yuen et al, 2021 ). These impacts may be due in part to methylation changes; maternal plasma glucose is associated with serotonin transporter gene ( SLC6A4 ) methylation in placenta, which may be risk factor for later serotonin dysregulation and neurodevelopmental diagnoses, as discussed below (section 3.1 ) ( Song et al, 2022 ).…”
Section: Studies Of Placental Disease and Neuropsychiatric Riskmentioning
confidence: 99%
“…Gestational diabetes causes placental immaturity, necrosis, and hyper-angiogenesis ( Jarmuzek et al, 2015 ), and is linked with offspring developmental delay ( Sun et al, 2022 ) and cognitive dysfunction ( Ahmed et al, 2023 ; Van Dam et al, 2018 ), among other neurodevelopmental outcomes ( Shao et al, 2021 ) revealed by clinical studies. The gestational diabetes medication metformin is also linked to placental metabolic and differentiation phenotypes ( Nashif et al, 2023 ) as well as child neurodevelopmental abnormalities ( Deussen et al, 2023 ; Yuen et al, 2021 ). These impacts may be due in part to methylation changes; maternal plasma glucose is associated with serotonin transporter gene ( SLC6A4 ) methylation in placenta, which may be risk factor for later serotonin dysregulation and neurodevelopmental diagnoses, as discussed below (section 3.1 ) ( Song et al, 2022 ).…”
Section: Studies Of Placental Disease and Neuropsychiatric Riskmentioning
confidence: 99%
“…Indeed, several studies have demonstrated that metformin promotes osteogenic, neuronal, myogenic, and adipogenic differentiation with varying results (Zhan et al, 2020;Ould-Brahim et al, 2018;Dadwal et al, 2015;Ahn and Cho, 2017;Fatt et al, 2015;Smieszek et al, 2018). Metformin induces cell proliferation at low concentrations' but it has anti-tumor activity at higher concentrations and can inhibit the proliferation of cancer cells (Nashif et al, 2023). At present, research is limited to in vitro and experimental animal models, however it can be hypothesized that the contradictory effects of metformin might be dependent upon specific cell types and/or dose differences.…”
Section: Metforminmentioning
confidence: 99%